Analyzing sustainable energy in developing countries: Selected South African case studies - Howells, Mark Idwal (Energy Research Centre, 2014)
This thesis demonstrates the use of selected Energy-Environment-Economic (E3) modelling techniques to provide insight to developing country issues. The work focuses on analyzing combinations of technologies and energy use to satisfy potential requirements of consumers at the lowest cost to society. (Tools such as MARKAL- of the Energy International Energy Agency's (IEA) Technology Systems Analysis Program (ETSAP) - are used often). The thesis shows how these models may be adapted in novel ways to tackle different challenges in different contexts. The applications covered range from macro-economic problems to the micro-economic village level analysis of fuel and appliance use. The thesis demonstrates through a national (South African) analysis selected greenhouse gas (GHG) mitigation potentials. By examining markets in low-income areas dependent on biomass it shows relationships between institutional- and information-failure and traditional fuel use. Using the increased functionality available in the TIMES model (the successor to the afore-mentioned MARKAL), detailed dynamics of low income fuel use are simulated. By adopting simplifications, a robust, simple and critical analysis of an energy subsidy is made. Using a Multi-Criteria Decision Analysis (MCDA) approach a range of GHG mitigation options are compared in a developing country context. The thesis reports on environmentally friendly development paths derived from the application of the Goal Programming extension of MARKAL. Finally it questions the appropriateness of the Clean Development Mechanism's policy of supporting only 'additional' GHG mitigation in certain circumstances. In an appendix it develops an efficient industrial data collection process using an MCDA analysis. The main theme of this thesis is to show how suitable modelling can not only warn of inefficiency in development policies, but also indicate technical scenarios of how such inefficiencies are best remedied. Key words: South Africa, Energy-Environment-Economic Modelling, MARKAL, TIMES, Efficiency, MCDA, Greenhouse gas, Goal Programming, Clean Development Mechanism